Epigenetics and Pathology 2013
DOI: 10.1201/b16304-4
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Analysis of DNA Methylation in Human Amnion

Abstract: e amnion is a speciali�ed tissue in contact with the amniotic �uid, which is in a constantly changing state. To investigate the importance of epigenetic events in this tissue in the physiology and pathophysiology of pregnancy, we performed genome-wide DNA methylation pro�ling of human amnion from term (with and without labor) and preterm deliveries. �sing the Illumina In�nium HumanMethylation27 BeadChip, we identi�ed genes exhibiting differential methylation associated with normal labor and preterm birth. Fun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 51 publications
0
21
1
Order By: Relevance
“…Studies have suggested that maternal factors, including socioeconomic status [11], pre-pregnancy BMI [26], smoking during pregnancy [27] and nutrition status [28] affect the risk of PTB. DNA methylation partially explains the effects many of these factors [19][20][21][22][23][24][26][27][28]. In this study, we found associations of maternal BMI, delivery season and WBC count with PTB; however, these factors did not in uence the DNA methylation levels of VTRNA2-1 in maternal blood.…”
Section: Discussioncontrasting
confidence: 52%
See 1 more Smart Citation
“…Studies have suggested that maternal factors, including socioeconomic status [11], pre-pregnancy BMI [26], smoking during pregnancy [27] and nutrition status [28] affect the risk of PTB. DNA methylation partially explains the effects many of these factors [19][20][21][22][23][24][26][27][28]. In this study, we found associations of maternal BMI, delivery season and WBC count with PTB; however, these factors did not in uence the DNA methylation levels of VTRNA2-1 in maternal blood.…”
Section: Discussioncontrasting
confidence: 52%
“…DNA methylation changes in the amnion or foetal tissue were determined to be partially involved in the physiological process of PTB and in foetal development. [23,24]. Thus, the evaluation of genes containing these differentially methylated sites may be useful to identify biological pathways involved in PTB, thereby facilitating the identi cation of clinically informative biomarkers for the prediction of PTB.…”
Section: Introductionmentioning
confidence: 99%
“…38,44 DNA methylation patterns regulate the functional properties of immune cells 45,46 and associate with inflammatory markers, 47 chronic disorders, [48][49][50] and PTB. 27,51 We hypothesize that DNA methylation patterns may reveal genes whose regulation is unique to women who deliver preterm or provide insight into its intergenerational risk…”
Section: Introductionmentioning
confidence: 99%
“…Methylation of the third intron of the human OXTR was associated with repressive binding proteins from non-expressing peripheral blood leukocytes, while relative hypomethylation of this region was associated with myometrium from non-pregnant and term pregnancy (Mizumoto et al, 1997). Kim et al (2013) assessed some methyl sites in the 5' UTR of the OXTR in term, pre-term labored and term unlabored amnion. Methylation of the human OXTR gene predominantly at a site called MT2 contributes to tissue-specific repression of OXTR mRNA expression, in vitro (Kusui et al, 2001) and is associated with OXTR mRNA repression in human brain (Gregory et al, 2009).…”
Section: Gene By Environment Interactionsmentioning
confidence: 99%